Acyl Radical Addition onto Aza‐Baylis–Hillman Adducts: A Stereocontrolled Access to 2, 3, 5‐Trisubstituted Pyrrolidines. Issue 14 (8th June 2017) - Grélaud, Simon; Lusseau, Jonathan; Massip, Stéphane; Landais, Yannick
Abstract: Free‐radical addition of acyl radicals to chiral aza‐Baylis–Hillman adducts was shown to afford the corresponding 1, 4‐amino ketones in good yields and good 1, 2‐stereocontrol. These ketones were then elaborated further using conditions varying as a function of the nature of the N‐protecting group. Robust N–Ts protection thus allowed the formation, under acidic conditions, of a cyclic iminium which was reduced using bulky (Me3 Si)3 SiH into the corresponding 2, 3, 5‐pyrrolidine exhibiting a trans‐trans relative configuration. In contrast, under these conditions, the N‐Boc protecting group was removed, leading to the formation of stable dihydropyrroles, which were then hydrogenated with PtO2, leading to 2, 3, 5‐pyrrolidines having a trans‐cis relative configuration. When additional ketone or ester groups were present on the pyrrolidine skeleton, further cyclization led to indolizidinones and pyrrolizidines in good overall yield in 4 steps and two‐pot operations. Abstract :